Regarding the study of the anatomical collections of the criminal anthropology schools - Iorio, Silvia (Medicina Historica, 2022)
I find it very important to take a cue from the investigative method conducted by the authors Verderame and Borrelli and presented in the article Malformed skulls in criminal anthropology: a preliminary study on the Cranioteca of the Anthropology Museum of Naples published in the Journal of Medicina Historica. As a scholar of the History of Medicine who deals with criminal anthropology, I find the contribution of paleopathologists to be important in the study of the osteological collections of museums linked to the history of psychiatry in the 19th century. Mine also wants to be an invitation to increase the dialogue between the different skills also to enhance this type of anthropological heritage and awaken an interest in these issues also among the whole community.